2017
DOI: 10.1038/ng.3896
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 19 new risk loci and potential regulatory mechanisms influencing susceptibility to testicular germ cell tumor

Abstract: Genome-wide association studies (GWAS) have transformed our understanding of testicular germ cell tumour (TGCT) susceptibility but much of the heritability remains unexplained. Here we report a new GWAS, a meta-analysis with previous GWAS and a replication series, totalling 7,319 TGCT cases and 23,082 controls. We identify 19 new TGCT risk loci, approximately doubling the number of known TGCT risk loci to 44. By performing in-situ Hi-C in TGCT cells, we provide evidence for a network of physical interactions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 70 publications
(81 reference statements)
1
100
1
1
Order By: Relevance
“…Genetic basis of TGCT in the Spanish population, suggesting the need of a combination of several variants. Our results are in agreement with other GWAS [10][11][12][13][14][15][16][17][18][19][20][21][22] and with the last large-scale sequencing study recently performed in TGCT cases, 33 which indicate that although familial TGCT has a strong genetic component, 6 the genetic basis in this tumour is determined by coinheritance of multiple risk variants. [2][3][4][5][6] In order to confirm that the five identified variants could confer susceptibility risk to the TGCT development, we replicated our results in a second series from the TGCA and ExAC databases (Supporting Information Fig.…”
Section: Cancer Genetics and Epigeneticssupporting
confidence: 92%
See 2 more Smart Citations
“…Genetic basis of TGCT in the Spanish population, suggesting the need of a combination of several variants. Our results are in agreement with other GWAS [10][11][12][13][14][15][16][17][18][19][20][21][22] and with the last large-scale sequencing study recently performed in TGCT cases, 33 which indicate that although familial TGCT has a strong genetic component, 6 the genetic basis in this tumour is determined by coinheritance of multiple risk variants. [2][3][4][5][6] In order to confirm that the five identified variants could confer susceptibility risk to the TGCT development, we replicated our results in a second series from the TGCA and ExAC databases (Supporting Information Fig.…”
Section: Cancer Genetics and Epigeneticssupporting
confidence: 92%
“…Recent Genome Wide Association studies (GWAS) transformed our understanding of TGCT susceptibility. A group of 52 independent loci has been already identified to be associated with TGCT susceptibility, suggesting that a polygenic model fits better with the genetic landscape of the disease . Since no Spanish genetic studies have been performed to date, the aim of this work was to explore the genetic background of the Spanish population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, genome‐wide association studies have had remarkable success in identifying genetic risks associated with TGCT and have identified more than 40 risk loci (Fig. ) . These studies have shown that common allele variations in KITLG , known as stem cell factor, which encodes Kitl, is the strongest genetic risk factor for TGCT .…”
Section: Genomic Risk Factorsmentioning
confidence: 99%
“…Not surprisingly, many other risk loci were found in sex determination‐related gene regions, such as DMRT1 (9q24), GATA4 (8p23), DAZL (3p24) and PRDM14 (8q13) . DMRT1 encodes a transcriptional factor.…”
Section: Genomic Risk Factorsmentioning
confidence: 99%